Pengembangan Pengajaran Mahārah al-Kalām untuk Meningkatkan Kemampuan Bahasa Produktif Tingkat Tinggi: Taṭwīr Ta’līm Mahārah al-Kalām litaḥsīn al-Mahārāt al-Lugawiyyah al-Intājiyyah al-‘Āliyah - Yasin, Agus; Idris, Fahmi; Setia Dien Labolo, Sultan Nanta (Study Program of Arabic Language Teaching, 2023)
This research aims to describe the development of learning speaking skills to improve students' productive language skills at a high level. This research is qualitative research with the type of library research. The research data is in the form of discourse on the development of learning speaking skills for students, accessed from several recent e-journal research results. Data collection techniques are carried out using documentation. Meanwhile, data analysis uses content analysis. The research results show that the development of learning speaking skills for students is divided into three levels: beginner, intermediate, and advanced. At a high level it can be done using various techniques and methods so that the objectives and direction of learning speaking skills are by what was previously formulated. Learning speaking skills is important in training students to speak Arabic productively.